SOADM: A Design Architectural Method for Service-as-a-Software (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Service-Oriented Software Engineering is a new approach that concerns with methods to build software solutions as services and compositions with respect to service orientation and service-oriented architecture. Several methods from both academia and industry have been developed for service-oriented based systems. This work first questions â€œto what extent a solution provided by a method would conform to service orientation, particularly, how to examine the design decisions based on quality attributesâ€, and â€œto what extent the method would align solutions with problemsâ€. Next, it proposes a framework for shaping methods. The framework considers the perspectives. Then, it propose a SOADM, a method for developing Service-as-a Software (SaaS) in high level design based on functional requirements and quality attributes.